Rapid evaluation of the birdlife at the Research, Postgraduate and Amazon Conservation Center (CIPCA), Napo province, Ecuadorian Amazon - Shiguango-Yumbo, Wilmer A. (2020)
The Research, Postgraduate and AmazonConservation Center of the Amazon State Universityis located on the eastern side of the Ecuadorian AndesMountains, covering an area of approximately 2840hectares of primary and secondary forests. The aim ofthe present investigation was an inventory rapid of birdsin strata of secondary forest and in strata of intervenedareas (silvopastoral and agricultural interventions).Transect counts were made by observation and callrecordings to register the species, which were doneintensively during the months of April and May 2018.A total of 94 species were recorded in both study areascorresponding to 30 families, being the most abundantThraupidae (27.6%) and Tyrannidae (16%) which arevery common birds in intertropical zones. Secondaryforest strata were the most diverse with a Margalefindex of 10.5 and a Shannon index of 3.6. However, theintervened area shows a greater abundance regardingthe number of individuals per species, perhaps due to thepresence of fruit tree species. Species in risk categorieswere also determined according to International Unionfor Conservation of Nature, resulting in 13 specieswith high value for these categories, which should beconsidered important for conservation programs.